Concept of Advertising Activity and its Legal Essence (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
Advertising activity is an integral part of today's economic processes, it is important as a means of conveying information about goods and services to a wide audience and promoting their sale. This article discusses the concept of advertising activity, its main features and legal aspects. Legal procedures and rules applied in the advertising process help to effectively manage relations between entrepreneurs and consumers. Advertising legislation is especially important for protecting consumer rights and ensuring fair competition.